BOKO HARAM INSURGENCY AND NIGERIA’S FOREIGN POLICY:: A FAILURE OF DIPLOMACY, MULTILATERALISM AND SECURITY APPARATUS? - Omobuwajo, Olufemi Ajibola (Journal of Contemporary International Relations and Diplomacy, 2021)
International terrorism became a major concern to Nigeria with the emergence of the Boko Haram Islamist group from around 2009, and the escalation of attacks on the country by the sect. The group has bases in neighbouring countries of Chad, Niger, and Cameroon. This made the governments of Presidents Goodluck Jonathan and Mohammadu Buhari to be involved in negotiations, dialogues, shuttle diplomacy, and the usage of other tools of foreign relations with these contiguous countries. The Multinational Task Force (MNTF) was established in 1993 by Lake Chad Basin Commission and had to be resuscitated and invigorated by the governments of Jonathan and Buhari. However, the insurgency lingered despite these concerted efforts. This paper attempts to investigate why several foreign and security policy initiatives of the Nigerian government have failed to find lasting solutions to the insurgency. Secondary data, qualitative research methods, and content analysis were used as a methodology in this research. Findings showed that inefficiencies of government, poverty, and porous borders made it easier for Boko Haram terrorists to recruit members from these neighbouring countries. It was also revealed that this insurgency has made Nigeria lose foreign direct investment (FDI) because some Multinational Corporations (MNCs) relocated from the country. Therefore, the study advocates a wider approach that incorporates economic programs that would reduce poverty among the local populace and stronger border controls, among others.